Design and Formulation of Modified-Release Bilayer Tablets of Rosuvastatin and Ezetimibe (Bangladesh Pharmaceutical Journal, 2025)
Cardiovascular disease (CVD) causes a significant number of morbidity and mortality worldwide, primarily driven by dyslipidemia and abnormal lipid levels. Effective management of hyperlipidemia and CVD typically involves using various pharmacological agents, including statins (like atorvastatin and rosuvastatin), cholesterol absorption inhibitors (like ezetimibe), and fibrates. The combined use of these agents has been shown to decrease cardiovascular events effectively over a long duration. This study formulated and designed a bilayer tablet containing sustained-release formulations of rosuvastatin and immediate-release formulations of ezetimibe. The compatibility of drugs within themselves and with the release modifiers was confirmed using FTIR and DSC. The effectiveness of the formulations was evaluated by in-vitro dissolution studies and release kinetics. The release of the ezetimibe was 90% within 60 minutes, whereas rosuvastatin was released 90% from its sustained release formulation within 6 hours. The release rates were evaluated with the Higuchi model, Korsmeyer-Pappas model, and first-order kinetics, revealing the best ezetimibe formulation containing cross-povidone and the best rosuvastatin formulation containing methocel K4M. The combined use of the two formulations would ensure a rapid onset of action and an effective release profile over a long duration.Bangladesh Pharmaceutical Journal 28(1): 70-82, 2025 (January)